Juridical Analysis of Legal Protection for Healthcare Volunteers in Disaster Areas - Y.Aritonang; Z.Tobing (The Medical Journal of Hospital Management and Health Law, 2025)
Introduction: Healthcare volunteers play a critical role in disaster response, yet they often operate in high-risk environments with ambiguous legal safeguards. This study examines the adequacy of existing legal frameworks in providing comprehensive protection for these individuals. Methods: This study utilizes a normative juridical research method, analyzing statutory legislation, international humanitarian principles, and relevant legal doctrines concerning disaster management and healthcare workers. Results: The findings reveal that while general disaster management laws acknowledge volunteers, specific rights, liabilities, and safety guarantees for healthcare volunteers remain fragmented and insufficiently regulated. This regulatory gap leaves volunteers vulnerable to civil liability, occupational hazards, and lack of institutional support. Discussion: The discussion highlights that existing laws often conflate general community volunteers with specialized healthcare volunteers who face unique medical-legal risks. A comprehensive literature review underscores the necessity of establishing clear standard operating procedures, state-backed insurance, and explicit liability immunities similar to Good Samaritan laws adapted for disaster contexts to ensure systemic resilience. Conclusions: In conclusion, the current legal framework is inadequate to protect healthcare volunteers in disaster areas. It is recommended that the government enact specific derivative regulations that clearly define the rights, immunities, and welfare guarantees for these vital actors to foster a safer volunteer ecosystem.